Removal of lead from aqueous solution with nanofibrous nanocomposite of polycaprolactone adsorbent modified by nanoclay and nanozeolite. (December 2019) - Irandoost, Masoumeh; Pezeshki-Modaress, Mohamad; Javanbakht, Vahid
Graphical abstract: Abstract: Removal of heavy metals from aqueous solutions as hazardous, carcinogenic, and toxic pollutants is considered among the most important environmental issues in recent years. In this study, polycaprolactone nanofibrous adsorbent was prepared by the electrospinning method and then, was modified by clay mineral and zeolite nanoparticles and characterized by field emission scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, energy-dispersive X-ray spectroscopy, and finally, the lead removal ability at an aqueous solution was evaluated. The experiments were carried out intermittently under different process conditions. Then, the impact of effective parameters on lead adsorption process including the initial concentration of the metal solution, pH, the adsorbent amount, and temperature was studied. Also, kinetics, isotherm, and thermodynamics of the adsorption process were determined. The results demonstrated that the addition of clay mineral and zeolite nanoparticles to polycaprolactone have synergistic effect on lead adsorption capacity of nanofibers The results of adsorption processes showed that with increased pH up to 5.5, increased solution concentration up to 25 ppm, decreased adsorbent up to 0.01 g, and increased temperature up to 40 °C, the adsorbent value increased. Second-order pseudo-adsorption kinetics was observed and also lead adsorbent isotherm followed the Freundlich model. The thermodynamic results showed that lead adsorption process with synthetic adsorbent was a spontaneous process.